Phonetic of the National Anthem of Peru translated into Collao Quechua: Treatment in eyective consonants - Valdez Luna, Pool Kevin (2022)
The National Anthem of Peru translated into Collao Quechua is a musical work regularly performed in protocol events in the country, especially in its South Andean region by professional singers, choirs, and public and private institutions. However, this piece poses difficulties for its pronunciation due to non-Spanish phonemes that are frequently pronounced in a non-accurate way or present technical difficulty at the time of execution among non-Quechua-speakers, which becomes a communicative shortcoming in the performance of this work, even changing the meaning of the recited text. The study at hand addresses the phonetic analysis of the National Anthem of Peru translated into Collao Quechua with an emphasis on the location of phonemes foreign to the Spanish language, paying special attention to ejective phonemes or glottalic ejectives. These are explained in their form of sound mechanical functioning and guidelines have been provided so that they can be executed within the performers’ technical possibilities. Information tools have been used to give context to the work, such as the musical background of the National Anthem, the phonetic studies on the Collao Quechua, and the relationship that these have in the vocal performance. Subsequently, the National Anthem of Peru was analyzed phonetically in the Quechua language in order to locate the ejective consonants, which have been contrasted with three different executions, making a consensus among the allophone phonemes that may exist among these three to produce a more accurate transcription with the sound execution. Lastly, following the analysis carried out and the interview conducted with a performer, and based on previous phonetics and singing research, it is concluded that ejective consonants cause fatigue at a glottal level that could have a negative impact on the singer’s performance at the phonetic and physical phonatory levels when performing. However, as these consonants must be executed with the necessary clarity to be understandable by the listening audience, it is the singer’s responsibility to be able to find a balance according to their phonatory physical abilities.